2018
DOI: 10.1002/pros.23742
|View full text |Cite
|
Sign up to set email alerts
|

M2 macrophages and regulatory T cells in lethal prostate cancer

Abstract: Background Prostate cancer (PCa) is one of the most frequently diagnosed cancers in the world. Emerging evidence suggests that inflammatory cells such as M2 macrophages and regulatory T cells (T regs ) can contribute to cancer progression by suppressing the anti‐tumor immune response. This study investigated the number of CD163‐positive M2 macrophages in PCa tissue. It also investigated the correlation and interaction of M2 macrophages and T regs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
119
1
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(131 citation statements)
references
References 36 publications
8
119
1
3
Order By: Relevance
“…For the cluster 3 group which has a poor prognosis, the proportion of memory B cells, M2 macrophages and Treg cells was signi cantly higher than that of cluster 1 and cluster 2. This is consistent with previous studies [16][17][18]. M2 macrophages and Treg cells are immunosuppressive cells that inhibit immune activation in tumors and promote the development of tumors.…”
Section: Differences In Immune Cell Abundance Among Methylation Subtypessupporting
confidence: 93%
See 1 more Smart Citation
“…For the cluster 3 group which has a poor prognosis, the proportion of memory B cells, M2 macrophages and Treg cells was signi cantly higher than that of cluster 1 and cluster 2. This is consistent with previous studies [16][17][18]. M2 macrophages and Treg cells are immunosuppressive cells that inhibit immune activation in tumors and promote the development of tumors.…”
Section: Differences In Immune Cell Abundance Among Methylation Subtypessupporting
confidence: 93%
“…Erlandsson et al [16] found that the higher the degree of tumor in ltration of M2 macrophages was, the greater the risk of death in patients with prostate cancer; the high degree of in ltration of M2 macrophages with a good prognosis and an enhanced response to chemotherapy [32]. WooJR et al [18] found that the degree of B lymphocyte in ltration in prostate cancer tissues was higher than that in adjacent tissues, and the degree of B lymphocyte in ltration in patients with a high risk of recurrence was higher than that in patients with a low risk of recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…In the onco-immunity field, the role of tumor-associated macrophages, or TAMs, has recently gained great importance, since these can contribute to tumor progression, by promoting genetic instability and supporting metastasis. Furthermore, TAMs play a fundamental role in the response to cytoreductive therapy (chemotherapy and radiotherapy), where they can antagonize the antitumoral activity of these treatments [57,58]. Today, TAMs are considered sensitive therapeutic targets for immunomodulation of the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…The Tregs, through their immunosuppressive effects, favor tumorpromoting characteristics; and the same has been demonstrated in PC patients, in whom elevated levels of Tregs conferred poor survival rates and a greater possibility of death. 38 Various immune populations are trafficked to the tumor site, and Treg trafficking is mainly mediated through the production of CCL17 and CCL22 by tumor-infiltrating T cells and TAMs through the CCL17/CCL22:CCR4 axis. 21…”
Section: T Lymphocytesmentioning
confidence: 99%
“…36 The CD163 marker (alias, the scavenger receptor that is more specific to the M2 macrophage) is indicative of poor prognosis in PC. 38 A growing body of evidence suggests that the chemokines secreted in the TME of PC by TAMs mediate activation of the CCL2:CCR2, CCL17:CCR4, and CCL22:CCR4 pathways, thereby promoting PC progression. 19 In the laboratory, Izumi et al 20 studied the role of TAMs in PC metastasis and demonstrated a role for the CCL2/CCR2-mediated STAT3 and the CCL17/ CCL22:CCR4 axis in PC progression.…”
Section: Tumor-associated Macrophagesmentioning
confidence: 99%